Antecedents and Outcome of Trainees’ Motivation: Evident from South East Asia - Mohamad, Nur Izzaty; Ismail, Azman; Abd Rahman, Ishak; Zihni Tunca, Mustafa; Pusparini, Elok Savitri; Rino, Rino (The South East Asian Journal of Management, 2023)
Research Aims: This study examines the effect of training content on trainee outcomes and the mediating role of trainees’ motivation in the relationship between training content and organisational citizenship behaviour. Design/Methodology/Approach: A cross-sectional research design was employed to collect 320 survey questionnaires from employees at the Malaysian federal government’s central agencies in Kuala Lumpur Federal Territory. The SmartPLS software programme was utilised to assess the quality of the instrument and subsequently test the hypotheses. Research Findings: The results demonstrate that training content significantly determines trainee outcomes. Trainees’ learning motivation significantly mediates the relationship between training content and organisational citizenship behaviour. Theoretical Contribution/Originality: This study reveals that training motivation mediates the relationship between training content and organisational citizenship behaviour in the organisational sample. This finding supports and broadens previous studies conducted in South East Asian and other countries. Managerial Implication in the South East Asian context: The study findings can assist managers in understanding different paradigms of trainees’ motivation construct and formulate employee-oriented training instructions to maintain and upgrade organisational sustainability. Research Limitation & Implications: This study has certain methodological and conceptual limitations that must be addressed in future research to strengthen its findings.